Environmental stress, ageing and glial cell senescence: a novel mechanistic link to Parkinson's disease?. (22nd April 2013) - Chinta, S. J.; Lieu, C. A.; DeMaria, M.; Laberge, R.‐M.; Campisi, J.; Andersen, J. K.
Abstract Exposure to environmental toxins is associated with a variety of age‐related diseases including cancer and neurodegeneration. For example, in Parkinson's disease (PD), chronic environmental exposure to certain toxins has been linked to the age‐related development of neuropathology. Neuronal damage is believed to involve the induction of neuroinflammatory events as a consequence of glial cell activation. Cellular senescence is a potent anti‐cancer mechanism that occurs in a number of proliferative cell types and causes the arrest of proliferation of cells at risk of malignant transformation following exposure to potentially oncogenic stimuli. With age, senescent cells accumulate and express a senescence‐associated secretory phenotype (SASP; that is the robust secretion of many inflammatory cytokines, growth factors and proteases). Whereas cell senescence in peripheral tissues has been causally linked to a number of age‐related pathologies, little is known about the induction of cellular senescence and the SASP in the brain. On the basis of recently reported findings, we propose that environmental stressors associated with PD may act in part by eliciting senescence and the SASP within non neuronal glial cells in the ageing brain, thus contributing to the characteristic decline in neuronal integrity that occurs in this disorder.